The Marginalised Nativism Strikes Back: Critical Discourse Analysis of the AfD Party’s Anti-Refugee Campaign in Germany - Sudjono, Raihanna Athaayaa Ari; Gunawan, Aditya Batara (UI Scholars Hub, 2023)
Born as a Eurosceptic party in 2013, the Alternative für Deutschland (AfD) Party shifted its agenda to anti-refugee and anti-Islamic issues after the 2015 refugee crisis in Europe. This shift is evident in the discourse of traditional campaign posters distributed during the 2017 federal election in Germany. This article aims to map and conduct a critical discourse analysis of the refugee crisis issues constructed by the AfD Party through traditional campaign posters. The author argues that the AfD Party's anti-refugee and anti-Islam discourse is significantly influenced by factors such as interests, ideology, and social, economic, and political conditions. This research identifies four main driving factors for the AfD Party discourse: firstly, opposition to the European Union's refugee quota policy and Angela Merkel's Open Door Policy; secondly, distinctions between German identity and Islamic culture; then, concerns about increasing crime rates and the demographic crisis. Apart from prioritizing nativism, the AfD Party also constructs that refugees and Islam (they) are not part of Germany. The AfD party acts as a savior to overcome the German people's (us) concerns about foreign threats to German identity and traditions by raising public awareness and blaming the German government for its failure to handle this problem.